2019
DOI: 10.1021/jacs.9b03950
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Material Engineering of Photocathodes Derivatized with Polyoxometalate-Supported {Mo3S4} HER Catalysts

Abstract: Molecular engineering of efficient HER catalysts is an attractive approach for controlling the spatial environment of specific building units selected for their intrinsic functionality required within the multistep HER process. As the {Mo 3 S 4 } core derived as various coordination complexes has been identified as one as the most promising MoS xbased HER electrocatalysts, we demonstrate that the covalent association between the {Mo 3 S 4 } core and the redox-active macrocyclic {P 8 W 48 } polyoxometalate (POM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 55 publications
(97 reference statements)
1
39
0
Order By: Relevance
“…These absorptions correspond to Mo IV -centered d-d transitions and E®Mo LMCT (with E = S, O) [18,19] which are characteristic of {Mo3S4} covalently linked to polyoxotungstate units. [20] Moreover, a study of a similar compound with a-A-[SiW11O39] 8as lacunary Keggin subunits reported that both {Mo3S4} units are almost electronically uncoupled. [16] At working concentrations, the portion of light absorbed by the [Ir] at 450 nm is about 47% while in the presence of thio-POM, the attenuation of light in the most concentrated solution equals 98.8% for 2 cm optical path of the reactor.…”
Section: Steady-state Absorption and Emissionmentioning
confidence: 99%
See 2 more Smart Citations
“…These absorptions correspond to Mo IV -centered d-d transitions and E®Mo LMCT (with E = S, O) [18,19] which are characteristic of {Mo3S4} covalently linked to polyoxotungstate units. [20] Moreover, a study of a similar compound with a-A-[SiW11O39] 8as lacunary Keggin subunits reported that both {Mo3S4} units are almost electronically uncoupled. [16] At working concentrations, the portion of light absorbed by the [Ir] at 450 nm is about 47% while in the presence of thio-POM, the attenuation of light in the most concentrated solution equals 98.8% for 2 cm optical path of the reactor.…”
Section: Steady-state Absorption and Emissionmentioning
confidence: 99%
“…[13] The resulting mixed Mo3S4-containing POM was shown to be a very efficient electrocatalyst for HER, functioning either in homogeneous or in heterogeneous conditions, as deposited co-catalyst on silicon photocathode. [14] Such a strategy was demonstrated as a general efficient approach to synthesize polymodular thio-POM species that exhibit various combinations, stoichiometries and structures. [15] In context, we report on the combination of the {Mo3S4} core with the monovacant anion a-A-[PW11O39] 7resulting of a similar structure scheme of that previously reported for the [{(SiW11O39)Mo3S4(H2O)3(µ-OH)}2] 10cluster.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…而在王恩波团队 [37] [35,37,64,66,67] . [82] ; (b) {Mo 9 S 12 }/PEDOT光阴极的光致析氢示意图; (c, d) 析氢实验前后, {Mo 9 S 12 }/PEDOT的扫描电子显微镜图 [83] (网络版彩图) [85] ; (b)在改变IO 3 − 浓度的Na 2 SO 4 -H 2 SO 4 溶液中的电流-时间响应曲线 [86] (网络 版彩图) Figure 11 (a) Schematic illustration on the preparation of {P 8 W 48 }-Cu@Ag composite film [85], and (b) current-time response curve with varying concentrations of IO [87] ; (b) 杂化材料{P 8 W 48 }-ZrO 2 的制备过 程示意图 [90] (网络版彩图)…”
mentioning
confidence: 99%
“…a) The synthetic steps of P 8 W 48 @rGO composite[82]; (b) the schematic diagram for hydrogen evolution by {Mo 9 S 12 }/PEDOT photocathode; and the SEM pictures of {Mo 9 S 12 }/PEDOT (c) before and (d) after HER experiment[83] (color online).…”
mentioning
confidence: 99%